Using open innovation to identify the best ideas - King, Andrew; Lakhani, Karim R. (MIT, 2013)
As innovation becomes more democratic, many of the best ideas for new products and services no longer originate in well-financed corporate and government laboratories. How can companies tap into distributed knowledge and diverse skills? Increasingly, organizations are considering using an open-innovation process, but many are finding that making open innovation work can be more complicated than it looks. The authors' research suggests that executives in numerous industries face the same fundamental decisions when exploring open innovation: (1) whether to open the idea-generation process, (2) whether to open the idea-selection process or (3) whether to open both. The key to success, the authors argue, is careful consideration of what to open, how to open it and how to manage the new problems created by the openness. Although the authors found that many managers were fearful about venturing into an entirely new type of innovation process, they maintain that open innovation is rooted in classic innovation principles such as idea generation and selection. The first benefit of open innovation is the number of ideas that become available. Statistically, the more ideas generated, the better the quality of the best one is likely to be. A second, lesser-known advantage of open innovation is that the value of the best idea generally increases with the variability of the ideas received. There are advantages to casting the net widely enough to access ideas of diverse quality: The quality of the average idea may fall, but the best idea is more likely to be spectacular. While managers are often apprehensive about idea creation through open innovation, many are completely unfamiliar with the possibilities offered by opening idea selection. They assume that only company employees can make good choices about which ideas are best. Yet the authors found that outsiders provide distinctive expertise and perspectives, which enable companies to pick winning ideas and generate significant value. This is particularly true with products that can be used in many ways, or when fashions or requirements change quickly. A potential problem in open innovation, the authors point out, relates to how companies contract with idea generators. A second challenge in managing open innovation is caused by a shift in who bears the cost (and risk) of idea generation. With open innovation, the company pays for a design only after it has been completed. This means that the idea gene ...